Evaluasi dan Perbaikan Desain Antarmuka Pengguna pada Website Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Provinsi Sumatera Barat menggunakan Metode Human Centered Design (HCD) - Hanifah Asri; Satrio Hadi Wijoyo; Suprapto Suprapto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The DPMPTSP website is a medium for disseminating information related to investment potential and also the regulations used by DPMPTSP Prov. West Sumatra. Since it was first created, namely in 2017 the DPMPTSP website has never been evaluated and when it was evaluated for the first time by researchers using the User experience questionnaire (UEQ) which was distributed to 25 respondents with a purposive sample technique, the DPMPTSP website received an average value of 0.191 where all aspects of the benchmark gets a Bad score. Human centered design (HCD) approach is used in the design process. HCD is used to find out problems in the system and how to overcome these problems which involves a human perspective at each stage by focusing on the user and producing recommendations for design improvements to the user interface design. Wireframe and high-fidelity prototype are designs resulting from this research. After improving the user interface design, the test was carried out again using UEQ with the same number of respondents, namely 25 people and got a good response which got an average score of 1,800 where all aspects of the Benchmark got an Excellent score